Hidden genius of emotion - "Magai, Carol and" (Cambridge, 2002)
This thoughtful and beautifully written book demonstrates compellingly that emotions are central to personality development across the lifespan. Carol Magai and Jeannette Haviland-Jones draw on a wealth of textual and film material to forge an original empirical and theoretical analysis of the dynamics of emotion in human development. For its content, the work examines the lives of three mid-century psychologists, Carl Rogers, Albert Ellis, and Fritz Perls. Each man adopted a unique stance on the question of emotion in personality and in therapeutic interventions and, tellingly, the therapeutic methods they developed necessarily reflected their own emotional dynamics. Drawing on the most important research in clinical, social, and personality psychology, the authors reveal the pervasive influence of emotional organization in the lives of these individuals. Having presented a new approach to personology, autobiography, autobiography, narrative studies, psychotherapy and the theory of emotions on its publication in 2002, this book is essential reading.
Keywords: Personality and emotions